Dental Anxiety Amongst Pregnant Women: Relationship With Dental Attendance and Sociodemographic Factors - Soha AlRatroot; Gadah Alotaibi; Fai AlBishi; Shahd Khan; Muhammad Ashraf Nazir (Elsevier, 2022)
Introduction: : Access to oral care during pregnancy is important for the maintenance of optimal oral health. Objective: : The aim of this study was to estimate dental anxiety (DA) and its association with previous dental visits and sociodemographic factors amongst pregnant women. Methods: : A cross-sectional study was conducted (June through August 2019) amongst pregnant women (N = 825) attending hospitals and health centres in Dhahran, Khobar, and Dammam cities in the Eastern province of Saudi Arabia. The Modified Dental Anxiety Scale (MDAS) was used to assess DA and the World Health Organization Oral Health Survey for Adults was administered to evaluate patterns of dental attendance. Results: : DA was found in 90.9% of the pregnant women. The mean DA score of the sample was 12.53 ± 5.33 (range, 5 to 25) and it was significantly higher amongst non-Saudi (13.21 ± 5.24) vs Saudi women (12.15 ± 5.34) (P = .006), those who had negative dental experience (13.99 ± 5.62) vs those without such experience (12.2 ± 5.21) (P < .001), and those with dental pain or discomfort (13.18 ± 5.46) vs without pain or discomfort (11.94 ± 5.14) (P = .001). The study found a significant relationship between DA and reasons for dental attendance before pregnancy (P = .002) and time since the last dental visit (P = .009). Multiple logistic regression analysis showed significantly increased odds (OR, 1.69; 95% CI, 1.25 to 2.27) of experiencing moderate to extreme DA amongst pregnant women who visited the dentist after a year/never visited compared to those who visited in less than a year. Similarly, participants with negative dental experience were significantly more likely to have moderate to extreme DA (OR, 1.49; 95% CI, 1.02 to 2.20) than those without negative experience after adjusting for sociodemographic factors. Conclusions: : DA was highly prevalent amongst pregnant women, which was significantly associated with negative dental experience, dental pain or discomfort, and reasons for and time since the last dental visit.